Magnetostratigraphic evidence for deep-sea erosion on the Pacific Plate, south of Mariana Trench, since the middle Pleistocene: potential constraints for Antarctic bottom water circulation. Issue 1 (2nd January 2016) - Deng, Xiguang; Yi, Liang; Paterson, Greig A.; Qin, Huafeng; Wang, Haifeng; Yao, Huiqiang; Ren, Jiangbo; Ge, Junyi; Xu, Hongzhou; Deng, Chenglong; Zhu, Rixiang
Abstract: The Antarctic Bottom Water (AABW) current plays a crucial role in storing and transporting heat, water, and nutrients around the world. However, it is impossible to monitor AABW in the Plio-Pleistocene by direct measurement. Hence, abyssal erosion was usually chosen as an effective indicator of the presence of the AABW in the Indian and Eastern Pacific Oceans during that period. Here, we report a high-resolution magnetostratigraphy of a gravity core, the JL7KGC-01A from the south of the Mariana Trench, northwest Pacific Ocean. The main results are as follows: (1) polarity data suggest that the sequence recorded the late Gauss chron to the early Brunhes chron, including the Jaramillo, Cobb Mountain, and Olduvai normal subchrons; (2) the sedimentary processes in the study area since 2.9 Ma show three stages of sedimentation: 83 cm/Ma during 2.9–1.2 Ma, 183 cm/Ma during 1.2–0.7 Ma, and no sedimentation since ~0.7 Ma; (3) the area south of the Mariana Trench experienced a significant change in the deposition rate at 1.2 Ma, which could be correlated with the intensified desertification in inland Asia, and experienced a prominent depositional hiatus since the early middle Pleistocene, which likely resulted from the enhanced/expanded AABW. Based on these new polarity data and comparisons with previous studies around the Pacific Ocean, we therefore propose that the AABW experienced a notable change during the early–mid Pleistocene transition.